2013
DOI: 10.1016/j.puhe.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing mobile food vendors (a.k.a. street food vendors)—methods, challenges, and lessons learned for future food-environment research

Abstract: OBJECTIVES Mobile food vendors (also known as street food vendors) may be important sources of food, particularly in minority and low-income communities. Unfortunately, there are no good data sources on where, when, or what vendors sell. The lack of a published assessment method may contribute to the relative exclusion of mobile food vendors from existing food-environment research. A goal of this study was to develop, pilot, and troubleshoot a method to assess mobile food vendors. STUDY DESIGN Cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 14 publications
(29 reference statements)
0
43
0
3
Order By: Relevance
“…† Such focus neglects alternative, often nonintuitive, food sources such as gas stations, hardware stores, clothing outlets, book sellers, general merchandisers, salons, pharmacies, and other retailers offering food and/or drink. 87 It also neglects impermanent sources of food that may also be relevant, such as street vendors (ie, mobile food vendors 75,76,[88][89][90] and farmers' markets [91][92][93] ). Certainly, the food environment is much broader than just select food stores and restaurants.…”
Section: Limitation 3: Inclusion Of Only a Limited Range Of Food Sourcesmentioning
confidence: 99%
“…† Such focus neglects alternative, often nonintuitive, food sources such as gas stations, hardware stores, clothing outlets, book sellers, general merchandisers, salons, pharmacies, and other retailers offering food and/or drink. 87 It also neglects impermanent sources of food that may also be relevant, such as street vendors (ie, mobile food vendors 75,76,[88][89][90] and farmers' markets [91][92][93] ). Certainly, the food environment is much broader than just select food stores and restaurants.…”
Section: Limitation 3: Inclusion Of Only a Limited Range Of Food Sourcesmentioning
confidence: 99%
“…There were also limitations: (1) being cross-sectional, this study shows correlation, not causality, (2) investigators were not able to speak with all identified vendors, but, crucially, interview participation did not differ by whether vending was “healthier”, “mixed”, or “less-healthy” (data not shown), (3) there is no way to verify if investigators identified all vendors since a great majority of vendors had no permits (Lucan et al, 2013) and there is no adequate government record or other list of vendors for enumeration, (4) investigators cannot comment on specific sales or whether vendors’ customers are local residents, the locally employed who live elsewhere, or transients; investigators can only assume, as others have,(Mwangi et al, 2002) that the kinds of items vendors offered were those that local customers (residents and/or others) tended to buy and consume, (5) results may not be generalizable to other communities.…”
Section: Discussionmentioning
confidence: 83%
“…Investigators covered all 42mi 2 of Bronx County, NY during usual business hours, requiring a total of l40 weekdays summer-fall 2010. (Lucan et al, 2013)…”
Section: Methodsmentioning
confidence: 99%
“…In addition, controlling the street food sold is challenging because of the difficulty encountered by food vendorsin applying sanitary regulations, the large number of food vendors and their mobility [35]. Strategies to address the assessment challenges that emerged in the research of Lucan et al [36] may help make mobile vendor assessments become more routine-like in food-environment research. There is also a need to generate food and personal hygiene, and to ensure an effective system of regular hygienic-sanitary examinations with vendors and regular sample collections of the foodstuffs sold to customers [37].…”
Section: Resultsmentioning
confidence: 99%